Rádio peão: estudo dos mecanismos, tipologia e os efeitos dos rumores nas organizações - Cardoso, Marison Simões (1995)
The main subject of this study, is the rádio peão, (the brasilian word to the american grapevine) and the rumor (or gossip) in organizations. It is basicaly a teory review, including the analysis of growing, transformations, types and classification of rumors, according to social and psycological approachs. It also analyses the research methods of studing. At the end, some organizational recomendations and sugestions of new approachs areavailable.